PENDIDIKAN PRAGMATIS-PROGRESIF ISLAMIC INTERNATIONAL SCHOOL (IIS) KEDIRI DI ERA INDUSTRI 4.0 - Intan Nuyulis Naeni Puspitasari (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2018)
In the industry industry 4.0 some schools in Indonesia are beginning to be aware of the urgency of global perspective education in line with the flow of pragmatism and progressivism. One of them is the Islamic International School (IIS) Kediri, a formal Islamic-based and internationally standardized school that provides space for its students to develop their potential creatively and dynamically. The learning system is modernity but it still upholds the values of humanity as well as Islamic values. In reality, the pragmatic-progressive education model of IIS Kediri is implemented in several aspects of educational vision, educational goals, curriculum, learning process, role of teachers and students in learning. Therefore, the existence of IIS Kediri is one of the empirical forms of how the principles of process-based education, experience, practice, and student-centered can be adjusted to met the needs of life so that the output of IIS is expected to be superior, competent and competitive human being.